Inﬂation-indexed bonds and nominal bonds : financial innovation and precautionary motives - Kang, Minwook (2021)
This paper introduces a two-period monetary general equilibrium model with proportional transaction costs on nominal and inflation-indexed bonds. This paper demonstrates that financial innovation on indexed bonds causes equilibrium interest rates of the nominal bond to increase when agents have precautionary saving motives. This result implies that ignoring precautionary motives would underestimate savers' welfare gain and overestimate borrowers' welfare gain from innovation on indexed bonds.